Natural Compounds Targeting Cancer-Associated Fibroblasts against Digestive System Tumor Progression: Therapeutic Insights - Kuan-Jung Chiu; Hsin-Ying Clair Chiou; Chi-Han Huang; Pin-Chun Lu; Hui-Ru Kuo; Jiunn-Wei Wang; Ming-Hong Lin (Biomedicines, 2022)
Cancer-associated fibroblasts (CAFs) are critical for cancer occurrence and progression in the tumor microenvironment (TME), due to their versatile roles in extracellular matrix remodeling, tumor–stroma crosstalk, immunomodulation, and angiogenesis. CAFs are the most abundant stromal component in the TME and undergo epigenetic modification and abnormal signaling cascade activation, such as transforming growth factor-β (TGF-β) and Wnt pathways that maintain the distinct phenotype of CAFs, which differs from normal fibroblasts. CAFs have been considered therapeutic targets due to their putative oncogenic functions. Current digestive system cancer treatment strategies often result in lower survival outcomes and fail to prevent cancer progression; therefore, comprehensive characterization of the tumor-promoting and -restraining CAF activities might facilitate the design of new therapeutic approaches. In this review, we summarize the enormous literature on natural compounds that mediate the crosstalk of CAFs with digestive system cancer cells, discuss how the biology and the multifaceted functions of CAFs contribute to cancer progression, and finally, pave the way for CAF-related antitumor therapies.